Bovine brucellosis in Pakistan; an analysis of engagement with risk factors in smallholder farmer settings. Issue 3 (8th April 2019) - Arif, Shumaila; Thomson, Peter C.; Hernandez‐Jover, Marta; McGill, David M.; Warriach, Hassan M.; Hayat, Khizar; Heller, Jane
Abstract: A cross‐sectional study was conducted to estimate the seroprevalence of bovine brucellosis in smallholder farms in seven regions in Pakistan, identify herd and individual level risk factors for seropositivity and assess the level of engagement of farmers with risk factors. In total, 1063 cattle and buffalo belonging to 420 herds in seven districts were sampled. The Rose Bengal test (RBT), indirect enzyme‐linked immunosorbent assay (I‐ELISA) and competitive enzyme‐linked immunosorbent assay (C‐ELISA) were used for the serological diagnosis of bovine brucellosis on all the serum samples. The associations between herd‐and animal‐level risk factors and seropositivity were investigated using logistic regression analyses. In addition, herd management practice scores, created to quantify the number of management practices undertaken that pose a risk for Brucella transmission, were calculated and compared between seropositive and negative herds within each district. Overall herd and animal prevalence were estimated to be 16.2% (95% CI, 13–20%) and 8.7% (95% CI, 7.2–10.6%), respectively, across all districts sampled. Herds with a history of last trimester abortion were found to be more likely to be positive than herds without such history (OR = 2.06, 95% CI, 1.09–3.89), providing validation of our findings and identifying that clinical disease is occurring in this region. It was also identified that herds with five to eight buffalo (OR = 3.80, 95% CI, 1.69–8.49), and those with more than eight buffalo (OR = 3.81, 95% CI, 1.51–9.58) were more likely to be positive for Brucella than those with less (one to two and three to four) buffaloes present in the herd. The presence of other domestic animals at the farm and purchasing animals in last year were found to have no association with seropositivity. The findings of this study support the need for the development of targeted intervention strategies specific to the disease status of each district. Abstract : A cross‐sectional study was conducted to estimate the seroprevalence of bovine brucellosis in smallholder farms in seven regions in Pakistan, identify herd and individual level risk factors for seropositivity and assess the level of engagement of farmers with risk factors. The findings of this study support the need for the development of targeted intervention strategies specific to the disease status of each district.